Principles of Free Electron Lasers - Freund, H. P.; Antonsen, Jr., T. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents a comprehensive description of the physics of free-electron lasers starting from the fundamentals and proceeding through detailed derivations of the equations describing electron trajectories, and spontaneous and stimulated emission. Linear and nonlinear analyses are described, as are detailed explanations of the nonlinear simulation of a variety of configurations including amplifiers, oscillators, self-amplified spontaneous emission, high-gain harmonic generation, and optical klystrons. Theory and simulation are anchored using comprehensive comparisons with a wide variety of experiments.
Chapter 1. Introduction -- Chapter 2.The Wiggler Field and Electron Dynamics -- Chapter 3.Incoherent Undulator Radiation -- Chapter 4. Stimulated Emission: Linear Theory -- Chapter 5.NonLinear Theory: Guided Mode Analysis -- Chapter 6. NonLinear Theory: Optical Mode Analysis -- Chapter 7. Sideband Instabilities -- Chapter 8. Coherent Harmonic Generation -- Chapter 9. Oscillator Theory -- Chapter 10. Oscillator Simulation -- Chapter 11. Wiggler Imperfections -- Chapter 12. X-Ray Free Electron Lasers and Self-Amplified Spontaneous Emission (SASE) -- Chapter 13. Optical Klystrons and High-Gain Harmonic Generation -- Chapter 14. Electromagnectic-Wave Wigglers -- Chapter 15. Chaos in Free Electron Lasers.
Keywords: Telecommunication; Lasers; Electronics; Microwaves, RF Engineering and Optical Communications; Laser; Electronics and Microelectronics, Instrumentation